Opportunities and risks of a due diligence law: Brief report on behalf of the IMPULS-Foundation - Gabriel Felbermayr; Olivier N. Godart; Rolf J. Langhammer; Alexander-Nikolai Sandkamp (IMPULS-Foundation for mechanical engineering, plant engineering, and information technology, 2021)
A brief expert report by the Kiel Institute for the World Economy for the IMPULS Foundation analyzes the effects of the law on corporate due diligence in supply chains, which was passed by the German parliament in June 2021. Key findings are that suppliers from developing countries may be deprived of the opportunity to prosper through trade and that the international division of labor will decline. In the worst case, this could lead to a deterioration of the human rights situation in several countries. Mechanical engineering in Germany is particularly affected. For the design of a supply chain law, particularly at the European level, this short report therefore proposes a negative list approach as an alternative. – – Ein Kurzgutachten des Instituts für Weltwirtschaft in Kiel für die IMPULS-Stiftung analysiert die Auswirkungen des Sorgfaltspflichtengesetzes, das im Juni 2021 vom Bundestag beschlossen wurde. Zentrale Ergebnisse sind, dass einigen Zulieferern aus Entwicklungsländern die Möglichkeit genommen wird, durch Handel zu Wohlstand zu kommen, und dass die internationale Arbeitsteilung zurückgeht. Dies könnte die Menschenrechtslage in einigen Ländern schlimmstenfalls noch verschlechtern. Besonders betroffen ist der Maschinenbau in Deutschland. Für die Ausgestaltung eines Lieferkettengesetzes insbesondere auf europäischer Ebene schlägt dieses Kurzgutachten daher einen Negativlistenansatz als Alternative vor.
Keywords: 330; Supply chain; Global value chain; Working conditions; Corporate social responsibility; Impact analysis; Mechanical engineering; Plant engineering; Germany; Lieferkette; Globale Wertschöpfungskette; Arbeitsbedingungen; Corporate Social Responsibility; Recht; Wirkungsanalyse; Maschinenbau; Anlagenbau; Deutschland